Deteksi Spesies Brucella pada Kambing di Rumah Potong Hewan Jakarta - Mujiatun Mujiatun; Retno Damajanti Soejoedono; Etih Sudarnika; Susan Maphilindawati Noor (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Brucellosis is a zoonosis and occupational diseases transmision. The diseases caused by bacterial and attack multiple species of animals. Common species that infects goats as the most pathogenic species (zoonotic) is Brucella melitensis; however, the species B. abortus could also infect goats. The study purposed to find out the brucellosis seropositive in goat in Jakarta slaughterhouse and to detect caused agent of brucellosis. Sampling was done through slaughtered goats that come from brucellosis endemic area. The samples were collected fromslaughtered mature female goats i.e serum, goat milk, vaginal swab, mamary gland, limphoglandula supramamary, limph, and uterus. The detection method was used i.e patological lession, serological, culture and PolymeraseChain Reaction (PCR) technique. The serological detection of brucellosis in goats was done parallelly between Rose Bengal Test (RBT), Complement Fixation Test (CFT) and Enzyme Linked Immunosorbent Assay (ELISA). The results of this study demonstrated that out of the 119 serum samples serologically tested, negative for RBT, one was positive for CFT and none were positive with ELISA. Patological observation in the Brucella predilection organs, there were 5 goat carcases showed pathological lession (vagina discharge, hemoragy at limphand limphoglandula, crumbly limph and there were pus in uterus). The serum samples that had reacted positively and the organs with pathological lesion were confirmed further with PCR, bacterial isolation and identification.The PCR test results and the culture of milk samples, vaginal swabs and organs did not reveal any Brucella spp bacteria (B. abortus, B. melitensis, B. ovis dan B. suis) and also vaccine strains of RB51. Based on these results, it was concluded that brucellosis in goats on Java Island was a 0.84% seropositive (confidence interval 95%; 0.00826 - 0.00854) (1/119), although the species of Brucella that had infected them remains unknown.